The effect of discontinuing iron supplementation on the iron status of women - Gannon, Greg Allan (My University, 1992)
Twenty four women were studied in order to examine the effect that discontinued iron supplementation has on the hematological values of serum ferritin, serum iron and hemoglobin. Initially, 111 female volunteers were screened for iron deficiency by blood analysis (serum ferritin below 20 µg/L and/or hemoglobin below 120 g/L). On the basis of ferritin and hemoglobin measurements, 44 women (39.6%) qualified as iron deficient. Twenty four of the selected women completed the 24 week study. Mean age was 27.6 ± 7.5 years (range 18 to 40 years). Each of the subjects received the treatment of oral iron supplements (320 mg ferrous sulfate= 100 mg elemental iron taken as SLOW-Fe twice a day) for 12 weeks. Supplementation was then discontinued for an additional 12 weeks. Measurements of serum ferritin, serum iron and hemoglobin were taken at o, 6, 12, 18 and 24 weeks of the study. Statistical analysis using analysis of variance (ANOVA) indicated significant changes (p<.05) in serum ferritin and serum iron values. No significant (p<.05) change was found in hemoglobin values over the course of the study. Student-Newman-Keuls post hoc test was used to identify specific mean differences when a significant F ratio was observed. Serum ferritin values were significantly (p<.05) increased following 6 (11.5 ± 5.3 to 26.4 ± 14.3 µg/L) and 12 (11.5 ± 5.3 to 30.6 ± 14.9 µg/L} weeks of oral iron supplementation. Twelve weeks of discontinued supplementation did not significantly (p<.05) alter serum ferritin values as noted by mean values of 29.0 ± 15.0 µg/L and 28.2 ± 17.1 µg/L for weeks 18 and 24, respectively. Serum iron values were significantly {p<.05) increased {15.9 ± 6.7 to 25.4 ± 15.6 µmol/L) after 6 weeks of oral iron supplementation. Serum iron values at 12, 18 and 24 weeks of the study were not significantly {p .05) different from the values at week O and week 6. It can be concluded that oral iron supplementation {320 mg ferrous sulfate= 100 mg elemental iron taken as Slow Fe twice a day for 12 weeks) was successful in raising serum ferritin values {from 11.5 ± 5.3 to 30.6 ± 14.9 µg/L) in iron deficient women. Within the limitations of this study, 12 weeks of discontinued oral iron supplementation does not pose a threat to the iron status of iron repleted women.
Keywords: Iron metabolism, absorption & balance; Body iron; Iron excretion, deficiency & supplementation; Serum ferritin, iron and hemoglobin